Analysis of the Impact of Customer Experience and Engagement on Satisfaction and Loyalty in the Body Shop's Omnichannel - Nurul Afiifah Ghifari; Arif Imam Suroso; Sufrin Hannan (Asian Journal of Social and Humanities, 2026)
This study examines the impact of customer experience and engagement on customer satisfaction and loyalty within the omnichannel strategy employed by The Body Shop in Indonesia. As the cosmetic and personal care market experiences rapid growth, it is essential for companies to deliver an integrated experience across both online and offline channels. A seamless and consistent customer experience across various touchpoints can significantly enhance customer engagement, which in turn drives satisfaction and fosters loyalty. The research employs a quantitative approach with purposive sampling, analyzing data using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that customer experience has a positive and significant effect on both engagement and satisfaction, which ultimately contributes to improved customer loyalty. The findings offer valuable insights for companies in shaping more effective omnichannel strategies, aiming to enhance customer satisfaction and loyalty in a sustainable manner. By understanding these dynamics, businesses can refine their approach to integrating online and offline experiences, ensuring they meet the evolving expectations of customers and strengthen long-term relationships. This research provides practical recommendations for companies in the cosmetic and personal care industry to remain competitive in an increasingly digital marketplace.